"PSYCHOLOGICAL FACTORS OF FORMATION OF MORAL CONCEPTS IN PRESCHOOL CHILDREN IN THE CONDITIONS OF GLOBALIZATION AND WAYS OF STRENGTHENING MENTAL HEALTH." (Universal International Scientific Journal, 2026)
This study scientifically analyzes the formation of moral concepts in preschool children in the context of globalization processes, their psychological factors, and ways to strengthen children's mental health. The study highlights the influence of the family environment, the educational process, peer relationships, and modern socio-cultural factors on the formation of children's moral concepts, social behavior, and personal qualities in preschool children. It also substantiates innovative psychological and pedagogical approaches aimed at ensuring children's mental health in the context of globalization, developing their emotional stability, and forming positive moral qualities. The results of the study are aimed at developing practical recommendations that support the formation of children as well-rounded individuals in preschool educational institutions and the family environment.
Keywords: Globalization, preschool children, moral concepts, psychological factors, mental health, personal development, moral education, emotional stability, family environment, preschool education, innovative approaches, socialization.